TRANSFORMASI HUKUM PERCERAIAN DALAM ISLAM DAN RELEVANSI HUKUM POSITIF DI INDONESIA - Jufrianto, Rahmat Riyanda Agusta (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study aims to analyze the forms of transformation in divorce law from the Jahiliyah era to Islamic law, as well as its relevance to positive law in Indonesia. In the Jahiliyah context, women were often treated as objects without rights in the divorce process, which was arbitrarily carried out by the husband. With the advent of Islam, significant changes occurred, emphasizing justice, the protection of women's rights, and a more regulated procedure for divorce, as outlined in the Qur'an and Hadith. The methodology employed is a literature review, examining Islamic legal sources and Indonesian legislation, including Law No. 1 of 1974 and the Compilation of Islamic Law. The findings reveal that Islamic law grants women the right to protection and justice in the divorce process, with an emphasis on the procedures that must be followed through the court to prevent arbitrary actions. Furthermore, this study finds that positive law in Indonesia seeks to integrate the principles of Sharia with the needs of modern society, thereby offering better protection for individuals, particularly women, in the divorce process. This research highlights the importance of understanding divorce law that is just and equitable in today's social context, as well as the necessity of consistent law enforcement to protect individuals' rights. Keywords:  Islamic Divorce; Law; Women's Rights.